2006
DOI: 10.1007/s11094-006-0208-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologically active substances from Ambrosia artemisiifolia. Part 2

Abstract: A new scheme of the isolation of all fractions of polyphenolic compounds from wormwood-leaved ambrosia (Ambrosia artemisiifolia L.) collected in the budding period is proposed. The main components in the total extract are phenolcarboxylic acids (ferulic, isoferulic, caffeic, chlorogenic acids and caffeic acid glycoside) coumarins (scopoletin, scopolin, esculetin, esculin, umbelliferone, skimmin), and flavonoids (jaceidin, quercetin, isorhamnetin, isorhamnetin-3-rutinoside, quercimeritrin, isoquercitrin, and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…presence of a wide range of defensive chemical agents against herbivores, such as sesquiterpenic lactones, monotherpenes, terpenoids, and polyacetylenic resins [37]. Within this family, the genus Ambrosia presents a remarkable physiological plasticity that allows it to adapt to a wide range of environmental conditions [38], a characteristic that might be explained, at least partially, by the secondary metabolites produced by the species of this taxon [39]. All members of the Ambrosia genus present a high content of sesquiterpenic lactones which possesses antibacterial, cytotoxic, and antifungal properties [40,41].…”
Section: Journal Of Nanotechnologymentioning
confidence: 99%
“…presence of a wide range of defensive chemical agents against herbivores, such as sesquiterpenic lactones, monotherpenes, terpenoids, and polyacetylenic resins [37]. Within this family, the genus Ambrosia presents a remarkable physiological plasticity that allows it to adapt to a wide range of environmental conditions [38], a characteristic that might be explained, at least partially, by the secondary metabolites produced by the species of this taxon [39]. All members of the Ambrosia genus present a high content of sesquiterpenic lactones which possesses antibacterial, cytotoxic, and antifungal properties [40,41].…”
Section: Journal Of Nanotechnologymentioning
confidence: 99%
“…However, many investigations into the composition and properties of A. artemisiifolia indicate that this species can serve a valuable source of biologically active substances. The extracts of this plant showed various bioactivities, such as molluscicidal [3], plant growth inhibitory [4], anti-inflammatory [5], antithrombin [6], antibacterial [7], insecticidal [8], hepatoprotective and hypolipemic activities [9]. On the other hand, the main chemical components of this species were identified as sesquiterpene lactones, which account for the antihelminthic, cardiotonic, antiinflammatory, analgesic, sedative (calming), antimalarial, anti-tumor, and other types of pharmacological activity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Parkhomenko et al observed hypolipaemic properties of polyphenolic fractions isolated from common ragweed in rats after inducing hyperlipidaemia by the joint per oral administration of vitamin D2 and cholesterol [182]. Their results are in agreement with the documented triglyceride level reduction in our study.…”
Section: Toxicological Evaluation Of Common Ragweedsupporting
confidence: 93%
“…The phytochemical investigations, beside the examination of the entire plant, are focusing mainly on the pollens. Flavonoids, phenolcarboxylic acids, and polyphenolic compounds have been reported from pollens and plant, as well [182,183]. The surface of the pollens is rich in proteins, peptides with immunoglobulin-E binding capacity (Amb a 1 and Amb a 2 allergens) with ability to trigger rhinitis, oculorhinitis and other symptoms of hay fever [184].…”
Section: Phytochemistry and Pharmacology Of Ambrosia Artemisiifoliamentioning
confidence: 99%
See 1 more Smart Citation